Interactions of phosphate solubilising microorganisms with natural rare-earth phosphate minerals: a study utilizing Western Australian monazite - Corbett, Melissa; Eksteen, Jacques; Niu, Xi-Zhi; Croue, Jean-Philippe; Watkin, Elizabeth (2017)
Many microbial species are capable of solubilising insoluble forms of phosphate and are used in agriculture to improve plant growth. In this study, we apply the use of known phosphate solubilising microbes (PSM) to the release of rare-earth elements (REE) from the rare-earth phosphate mineral, monazite. Two sources of monazite were used, a weathered monazite and mineral sand monazite, both from Western Australia. When incubated with PSM, the REE were preferentially released into the leachate. Penicillum sp. released a total concentration of 12.32 mg L-1 rare-earth elements (Ce, La, Nd, and Pr) from the weathered monazite after 192 h with little release of thorium and iron into solution. However, cultivation on the mineral sands monazite resulted in the preferential release of Fe and Th. Analysis of the leachate detected the production of numerous low-molecular weight organic acids. Gluconic acid was produced by all microorganisms; however, other organic acids produced differed between microbes and the monazite source provided. Abiotic leaching with equivalent combinations of organic acids resulted in the lower release of REE implying that other microbial processes are playing a role in solubilisation of the monazite ore. This study demonstrates that microbial solubilisation of monazite is promising; however, the extent of the reaction is highly dependent on the monazite matrix structure and elemental composition.